2005
DOI: 10.4028/www.scientific.net/kem.290.183
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Fracture Toughness Measurement of Thick Ceramic Coatings by Indentation

Abstract: The basic requirement for the use of a ceramic coating is sufficient adhesion to its substrate. A measure of the adhesive properties of a coating is the interfacial fracture toughness. The test method applicable for interfacial fracture toughness measurements depends on the mechanical properties of the material system and the geometry of the test piece. In this work, indentation methods have been evaluated for the estimation of the fracture toughness of ceramic thermal barrier coatings on metallic substrates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In contrary, the hardness dramatically increased with decreasing residual indent depth for films indented by the Cube-corner indenter. Indentation tests were also used to evaluate adhesion strength of the thermal barrier coatings (TBCs) which were used to improve the performance and efficiency of advanced gas turbines [34][35][36][37][38]. Indentation tests were also used to evaluate adhesion strength of the thermal barrier coatings (TBCs) which were used to improve the performance and efficiency of advanced gas turbines [34][35][36][37][38].…”
Section: Application Of Nanoindentation In Materialsmentioning
confidence: 99%
“…In contrary, the hardness dramatically increased with decreasing residual indent depth for films indented by the Cube-corner indenter. Indentation tests were also used to evaluate adhesion strength of the thermal barrier coatings (TBCs) which were used to improve the performance and efficiency of advanced gas turbines [34][35][36][37][38]. Indentation tests were also used to evaluate adhesion strength of the thermal barrier coatings (TBCs) which were used to improve the performance and efficiency of advanced gas turbines [34][35][36][37][38].…”
Section: Application Of Nanoindentation In Materialsmentioning
confidence: 99%
“…However, several methods have been investigated and proposed. These include utiliz ing the ''pull-out technique" that is traditionally used to study fibers in reinforced ceramics or metals [9], four-point bend testing with a notched coating that initiates the delamination [10], and indentation techniques [5,[11][12][13]. The indentation technique shows great promise, since it requires only minimum sample preparation along with small quantities of material and is easy to perform.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the technique proposed to evaluate the interfacial fracture toughness of TBCs shows great prom ise, some problems appeared when evaluating TBCs with thicker ceramic top coats and TBCs that have been sub jected to thermal aging [13]. An earlier experimental study [13] indicated that the technique developed in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations